A man from Bendery: L.S. Berg as geographer and loess scholar - Smalley, Ian; Markovic, Slobodan; O’Hara-Dhand, Ken; Wynn, Peter (Bogucki Wydawnictwo Naukowe, 2010)
Lev Semenovich Berg was born in Bendery, in Moldova. He had great success as an ichthyologist and geographer; he also proposed, in 1916, an interesting theory of loess formation. As a biologist he was persecuted by Lysenko and the Soviet state in the time of pseudo-science in the 1930s and 1940s. Despite his being persecuted, the loess theory became, in effect, the official Soviet theory of loess formation. This theory had to be compatible with his ‘landscape’ theory which did not find favour in Marxist-Leninist geography. Berg’s loess theory was very much a geographical theory, as opposed to the geological theory of aeolian deposition, which was accepted outside the Soviet Union. Berg was hugely successful in many fields, but his contributions to loess science tend to be neglected. His ‘soil’ theory of loess formation has been widely disparaged but still has some influence in Russia. The concept of loessification may still be relevant to the later stages of deposit formation; the slow transition from metastable to collapsible may be best described as loessification.
Keywords: Lev Semenovich Berg; Theories of loess formation; Landscape theory; Loessification